2020
DOI: 10.21053/ceo.2019.00780
|View full text |Cite
|
Sign up to set email alerts
|

Vestibulocochlear Symptoms Caused by Vertebrobasilar Dolichoectasia

Abstract: Objectives. Vertebrobasilar dolichoectasia (VBD), an elongation and distension of vertebrobasilar artery, may present with cranial nerve symptoms due to nerve root compression. The objectives of this study are to summarize vestibulocochlear manifestations in subjects with VBD through a case series and to discuss the needs of thorough oto-neurotologic evaluation in VBD subjects before selecting treatment modalities.Methods. Four VBD subjects with vestibulocochlear manifestations were reviewed retrospectively. V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(35 citation statements)
references
References 30 publications
0
25
0
Order By: Relevance
“…In this study, after SS resurfacing/reshaping, short-term (< 1 week) and long-term (> 1 year) changes in subjective symptoms were analyzed in all patients. The severity of PT was assessed subjectively by qualifying the loudness and annoyance of tinnitus via VAS ranging from 0 to 10 34 , 35 . All questionnaires were delivered the day before the operation, and during short-term (< 1 week) and long-term (> 1 year) follow-ups.…”
Section: Methodsmentioning
confidence: 99%
“…In this study, after SS resurfacing/reshaping, short-term (< 1 week) and long-term (> 1 year) changes in subjective symptoms were analyzed in all patients. The severity of PT was assessed subjectively by qualifying the loudness and annoyance of tinnitus via VAS ranging from 0 to 10 34 , 35 . All questionnaires were delivered the day before the operation, and during short-term (< 1 week) and long-term (> 1 year) follow-ups.…”
Section: Methodsmentioning
confidence: 99%
“…The hearing thresholds for seven different octave frequencies (0.25, 0.5, 1, 2, 3, 4, and 8 kHz) were evaluated using pure-tone audiometry in a soundproof booth. The mean hearing threshold was calculated using the average of the hearing thresholds at 0.5, 1, 2, and 4 kHz (Han et al, 2019;Shim et al, 2019;Bae et al, 2020;Huh et al, 2020;Lee et al, 2020b;Song et al, 2020). At each subject's initial visit, we obtained a structured history of the characteristics of tinnitus including its presence, laterality, and psychoacoustic nature (pure-tone or narrow-band noise).…”
Section: Audiological and Psychoacoustic Evaluationmentioning
confidence: 99%
“…6,7,17,18 It is notable that multiple cranial nerve involvement in patients with VBD is rarely reported. [7][8][9] Madhugiri et al 8 described a patient with diplopia owing to a left abduction deficit, together with ipsilateral facial pain and facial muscle twitches, attributed to compression of the abducens, trigeminal and facial nerves caused by VBD, respectively. Pham et al 7 reported a similar case, in which VBD resulting in both abducens and ipsilateral trigeminal nerve palsies.…”
Section: Discussionmentioning
confidence: 99%
“…6,7 In contrast, abducens, trochlear, vestibular, glossopharyngeal or vagus nerve impairment caused by neurovascular compression of VBD is uncommon. [7][8][9][10][11][12] Notably, multiple cranial nerve involvement in patients with VBD is extremely rare. [7][8][9] Herein, we present a case of a 33-year-old patient with symptoms of the abducens and vestibulocochlear cranial nerves which were relieved by antihypertensive therapy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation